2011
DOI: 10.1089/jwh.2011.2864
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cervical Cancer in Criminal Justice Settings

Abstract: Background: Women in criminal justice settings have an increased prevalence of cervical cancer compared with the general population. However, little is known about abnormal cervical cancer screening results among women in jail and community-based criminal justice settings. Thus, the aims of this study were to compare the prevalence of self-reported abnormal Papanicolou (Pap) test results in women in jail and under community criminal justice supervision and to examine factors associated with abnormal Pap tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 26 publications
2
25
1
Order By: Relevance
“…(Binswanger et al 2010) Injection drug and crack cocaine use among women is associated with a number of serious but treatable health conditions, including HIV and sexually transmitted diseases (Latka et al 2001; Shannon et al 2008) It is in the interest of public health to facilitate access to health care for criminal justice involved women in community settings. (Binswanger et al 2011) Among recently incarcerated women, the combined stigma of incarceration and drug use both increases their need for health services and makes these services harder to access (van Olphen et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…(Binswanger et al 2010) Injection drug and crack cocaine use among women is associated with a number of serious but treatable health conditions, including HIV and sexually transmitted diseases (Latka et al 2001; Shannon et al 2008) It is in the interest of public health to facilitate access to health care for criminal justice involved women in community settings. (Binswanger et al 2011) Among recently incarcerated women, the combined stigma of incarceration and drug use both increases their need for health services and makes these services harder to access (van Olphen et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer, the result of a sexually transmitted infection, is disproportionately present in the lives of women involved in the North American criminal justice system [2]. Examination of the backgrounds of women in this population provides some insight into the origins of these poor health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 13,000 new cases of cervical cancer reported each year in the U.S., the rate among women in the criminal justice system is four–five times greater than among non-incarcerated women [1, 2]. The few investigators who have studied this problem in jail/prison populations have found that although many women get screened for cervical cancer, less than half gain access to recommended follow-up for abnormal Papanicolaou (Pap) tests results, which may involve human papilloma virus (HPV) typing, colposcopy, removal of precancerous tissue or cervical cancer treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Women incarcerated in jails and prisons report multiple risk factors for human papilloma virus (HPV) and cervical cancer – histories of multiple sex partners (Binswanger et al, 2011; Fogel and Belyea, 1999), sexually transmitted infections (STIs) (Hale et al, 2009; Hogben et al, 2001), exchanging sex for money, drugs, or life necessities (Bond and Semaan, 1996; Magura et al, 1993), and tobacco use (Cropsey et al, 2004). Prevalence studies of HPV in correctional settings have shown rates ranging between 27 and 46 percent (Bickell et al, 1991; de Sanjosé et al, 2000; González et al, 2008).…”
Section: Introductionmentioning
confidence: 99%